2004
DOI: 10.1002/jnr.20239
|View full text |Cite
|
Sign up to set email alerts
|

Delayed neurotrophic treatment preserves nerve survival and electrophysiological responsiveness in neomycin‐deafened guinea pigs

Abstract: Benefits of cochlear prostheses for the deaf are dependent on survival and excitability of the auditory nerve. Degeneration of deafferented auditory nerve fibers is prevented and excitability maintained by immediate replacement therapy with exogenous neurotrophic factors, in vivo. It is important to know whether such interventions are effective after a delay following deafness, typical for the human situation. This study evaluated the efficacy of brain-derived neurotrophic factor (BDNF) and ciliary neurotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 63 publications
10
76
1
3
Order By: Relevance
“…Nerve growth factor (NGF) delivered alone (Shah et al, 1995), or a combination of BDNF, NT3, and neurotrophin-4/5 (Gillespie et al, 2004), enhanced neural survival when administration was delayed by 2 weeks. The combination of BDNF and ciliary neurotrophic factor (CNTF) enhanced auditory nerve survival even at delays of up to 6 weeks post-deafening (Yamagata et al, 2004). Consistent with an important role for FGF 1 in neurite outgrowth in the immature auditory system (Dazert et al, 1998;Hossain and Morest, 2000), we recently demonstrated the efficacy of BDNF plus FGF 1 in promoting systematic regrowth of the peripheral process of the auditory nerve even after a 6-week period of deafening (Miller et al, 2003b;2006a).…”
Section: Growth Factorsmentioning
confidence: 67%
“…Nerve growth factor (NGF) delivered alone (Shah et al, 1995), or a combination of BDNF, NT3, and neurotrophin-4/5 (Gillespie et al, 2004), enhanced neural survival when administration was delayed by 2 weeks. The combination of BDNF and ciliary neurotrophic factor (CNTF) enhanced auditory nerve survival even at delays of up to 6 weeks post-deafening (Yamagata et al, 2004). Consistent with an important role for FGF 1 in neurite outgrowth in the immature auditory system (Dazert et al, 1998;Hossain and Morest, 2000), we recently demonstrated the efficacy of BDNF plus FGF 1 in promoting systematic regrowth of the peripheral process of the auditory nerve even after a 6-week period of deafening (Miller et al, 2003b;2006a).…”
Section: Growth Factorsmentioning
confidence: 67%
“…Improved EABR thresholds have also been reported after intracochlear overexpression of BDNF by adenovirus ) and intracochlear infusion of CTNF (Yamagata et al 2004) or GDNF (Maruyama et al 2008;Scheper et al 2009). Our previous study demonstrated a marked 6-dB improvement in EABR thresholds over 10 weeks of BDNF infusion in neonatally deafened, developing cats (Leake et al 2011).…”
Section: Longitudinal Eabr Threshold Datamentioning
confidence: 83%
“…We postulate that the threshold of ABRs to acoustic stimulation improved through a direct trophic effect upon the auditory nerve and/or its synapse with the inner hair cells. Electrically evoked ABR thresholds have been shown to be reduced below pretreatment levels in deafened animals treated with BDNF (Shinohara et al 2002;Yamagata et al 2004;Shepherd et al 2005;Leake et al 2011). It therefore seems possible that treatment with neurotrophins may affect the auditory neurons in the hearing cochlea to a similar degree as the deafened cochlea.…”
Section: Discussionmentioning
confidence: 99%